2015
DOI: 10.1111/iji.12192
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of interleukin‐2, interleukin‐4, interleukin‐6, transforming growth factor‐β, tumour necrosis factor‐α and blood concentrations of calcineurin inhibitors in Turkish renal transplant patients

Abstract: Cytokines are essential for the control of the immune response as most of the immunosuppressive drugs target cytokine production or their action. The calcineurin inhibitors (CNIs) cyclosporine (CsA) and tacrolimus are immunosuppressive drugs widely used after renal transplantation to prevent allograft rejection. They are characterized by large interindividual variability in their pharmacokinetics; therefore, monitoring their blood concentrations is important to predict their optimal dosage following transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…In fact, other cytokines, including IL-2, IL-4, IL-6 and IL-18, can be selectively inhibited by tacrolimus [36] . Previous studies have reported genetic associations of IL-2, IL-4 and IL-6 with blood concentrations of calcineurin inhibitors [21] . Genetic polymorphisms in IL-18 (eg, rs5744247) and IL-10 (eg, -819 C/T and -592 C/A) can also affect TAC dose requirements [37,38] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, other cytokines, including IL-2, IL-4, IL-6 and IL-18, can be selectively inhibited by tacrolimus [36] . Previous studies have reported genetic associations of IL-2, IL-4 and IL-6 with blood concentrations of calcineurin inhibitors [21] . Genetic polymorphisms in IL-18 (eg, rs5744247) and IL-10 (eg, -819 C/T and -592 C/A) can also affect TAC dose requirements [37,38] .…”
Section: Discussionmentioning
confidence: 95%
“…However, these conclusions are controversial. There are also reports that polymorphisms in genes that participate in the pharmacodynamic (PD) pathway, including IL-2, IL-6, and IL-18, and genes involved in the immune system, for instance TLR4, can influence TAC pharmacokinetics [20][21][22] . The existing algorithms, including genetic and clinical factors, for TAC dose prediction only account for 40% to 60% of TAC dose variations [9,23] .…”
Section: Introductionmentioning
confidence: 99%
“…TAC tumor necrosis factor-α also decreases cytokines such as IL-1, -3, -4, -5, -6, and -8 [2]. CsA is another calcineurin inhibitor that decreases T-cell activity; moreover, it also decreases cyclosporine and neutrophil chemotaxis at TAC inflammation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are a number of studies on the effect of TAC on intestine anastomosis recovery, the number of studies examining the effect of CsA on intestine anastomosis are limited [12]. Whilst studies comparing the effects of the most commonly used immunosuppressive agents, TAC and CsA, on anastomosis recovery have been published, this study focuses on the evaluation of colon anastomosis cases after a short-term application of immunosuppressive drugs [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation